2006
DOI: 10.2105/ajph.2004.057232
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and Correlates of Daily Smoking and Nicotine Dependence Among Young Adults in the United States

Abstract: There are more common than unique correlates of each smoking stage and across racial/ethnic groups. Primary prevention and interventions addressing the factors tested could be uniform for most chronic smokers irrespective of dependence status and race/ethnicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

30
261
2
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 288 publications
(295 citation statements)
references
References 42 publications
30
261
2
2
Order By: Relevance
“…fewer symptoms of depression). These findings for depressive symptoms and perceived stress are contrary to those from the smoking literature, where both variables are associated with higher levels of tobacco dependence (John et al, 2006;Hu et al, 2006). Thus, in this cohort of male ST users, it does not appear as though more tobacco is used among men who report higher levels of perceived stress and/or depressive symptoms.…”
Section: Discussioncontrasting
confidence: 99%
“…fewer symptoms of depression). These findings for depressive symptoms and perceived stress are contrary to those from the smoking literature, where both variables are associated with higher levels of tobacco dependence (John et al, 2006;Hu et al, 2006). Thus, in this cohort of male ST users, it does not appear as though more tobacco is used among men who report higher levels of perceived stress and/or depressive symptoms.…”
Section: Discussioncontrasting
confidence: 99%
“…5 Although cross-sectional, [6][7][8][9][10][11] follow-up, [12][13][14][15] and longitudinal [16][17][18] studies of adolescents have shown a relationship between parental and child smoking, the overall body of research remains equivocal. 5 Previous studies have been limited by the use of retrospective reports of parent smoking, the use of offspring reports of parental smoking and other parent-level risk factors, and the lack of detailed measures encompassing the duration and intensity of parental cigarette use.…”
Section: Discussionmentioning
confidence: 99%
“…Second, we test for several confounders, such as parental education, marital status, employment, and gender, as well as child depressive affect, self-esteem, closeness to parents, grade point average (GPA), age, race/ethnicity, and gender. 1,2,11,15,17,19,[27][28][29][30][31][32][33] In addition, the single cohort reduces any confounding effects that may be attributable to differing ages of the parents at the various survey waves. Third, data collected directly from siblings allows a unique examination of the influence of older-sibling smoking, which has emerged as an important consideration in intergenerational research.…”
Section: Discussionmentioning
confidence: 99%
“…Given the critical timing of cigarette initiation during late adolescence (Breslau et al 2001;Hu et al 2006) in conjunction with findings suggesting that one-fifth of the variation in smoking among adolescents is between schools (Ennett et al 1997), schools make a particularly useful level at which to examine gene-environment interactions for smoking behaviors. In this paper we review the literature that links school characteristics to the likelihood that a student will begin to smoke and we focus on four distinct aspects of schools: (a) smoking prevalence; (b) student norms; (c) school policies; and (d) social demographic composition.…”
Section: Schools and Smokingmentioning
confidence: 99%